Treatment of high energy tibial plateau fractures with hybrid external fixator: intermediate term outcome - Jahan, Alamgir; Haseeb, Muhammad; Wazir, Fahad (International Journal of Research in Medical Sciences, 2017)
Background: High energy tibial plateau fractures pose a management challenge because of the complexity of bone and soft tissue trauma. Because of the frequency and magnitude of soft tissue of soft tissue injury in these fractures, early internal fixation becomes difficult. Wound breakdown and deep infection are common complications in plating of these difficult fractures. Primary management with hybrid external fixator can be a useful alternative to internal fixation in such cases. Methods: The study was a prospective case series done in the orhtopaedic department of a teaching hospital. 20 patients were studied. There were 13 Schatzker VI, 5 Schatzker V and 2 Schatzker IV fractures included. 4 patients had open fractures and 1 had compartment syndrome. Open fractures were operated in emergency department. Those with severe swelling and blisters were allowed few days to settle. Primary fixation using a hybrid external fixator was done. Mobilisation was started early. Patients were followed up to 1 year. Results: Union was obtained in all patients within 18 weeks. There was only deep infection. 95% patients had range of motion of 90 degrees or more. No patient had an extensor lag. Conclusions: Primary management of high energy tibial plateau fractures using hybrid external fixator is a reasonable option for cases that are not immediately amenable to internal fixation. It provides adequate stabilization to allow early motion and hastens patient rehabilitation. We have a good experience with this technique and recommend it for judicious use.